Hubungan Lingkungan dengan Pengendalian Demam Berdarah Dengue di Kecamatan Payung Sekaki Kota Pekanbaru - Sri Hardianti (Journal of Engineering Science and Technology Management (JES-TM), 2021)
This research was conducted in Payung Sekaki District, Pekanbaru City with the consideration that Payung Sekaki District, Pekanbaru City, is an area with the highest cases of dengue fever sufferers and deaths. This research was conducted from October to November 2020. The approach to this research was quantitative analysis with a cross-sectional research design by collecting data momentarily or only once at a time. The independent variable (environment) and the dependent variable (control of dengue hemorrhagic fever) were asked at the same time to respondents who are in Pekanbaru City in 2020. The population in this study are all Heads of Families (KK) in Payung Sekaki District, Pekanbaru City, namely as many as 21,254 families, the number of samples in this study was 100 respondents. The sampling technique in this study was purposive sampling, namely taking samples for a specific purpose based on predetermined inclusion and exclusion. Based on the results of research conducted in Payung Sekaki District, Pekanbaru City, the researchers can conclude that there is a significant relationship between the environment and the control of dengue hemorrhagic fever in Payung Sekaki District, Pekanbaru City